The Post-Unification German Labor Market - Holger Bonin; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2000)
This study surveys the development of the East German labor market after the unification of Germany. We explain that in the last decade, East Germans were faced with very high levels of joblessness that considering labor market exits and active labor market policy, are only partly reported as unemployment. A review of the evidence on the effectiveness of labor market policies suggests that job creation and training programs did not substantially promote reemployment, though they may have alleviated social burdens from unemployment. Discussing what causes the high unemployment in the east, we claim that effects of wage policy have been overrated. Differences in unemployment rates are also the result of more ample labor supply. We show that employment levels in the east have almost converged on western standards. The structure of employment, however, differs. Shortage of part-time work, service jobs and independent employment indicates that East Germany has failed to develop a service economy. We argue that unqualified adaptation to western procedures aggravated the investment and employment problem in the east.
Keywords: J40; O50; P27; 330; East Germany; unemployment; transitional economies; Arbeitsmarkt; Arbeitslosigkeit; Sektorale Beschäftigungsstruktur; Arbeitsmarktpolitik; Neue Bundesländer